A saúde mental de mães com bebês de 0 a 36 meses de idade face à pandemia de coronavírus - Dias, Perestrelo Marisa Bruno (2021)
Studies carried out in developing countries describe a progressive increase in mental disorders, with social and economic consequences. The present study investigated the relationship between sociodemographic factors and the prevalence of common mental disorders (CMD) in mothers, mostly residents in the southeastern region of the country, in times of the coronavirus pandemic, identifying the risk and protection factors. Method: a cross-sectional, quantitative study, carried out with a sample of 97 mothers of babies aged 0 to 36 months old, amidst the social distance from the Covid-19 Pandemic, in Brazil. The mothers answered a sociodemographic questionnaire and the Self Reporting Questionnaire of Minor Psychiatric Disorders (SRQ-20). Results: this sample had mostly white mothers residents of the southeastern region of the country, with an average age of around 34 years, mostly living with a partner, with at least 1 child and 40.1% of the sample has family income ranging from 4 to 10 minimum wages. The prevalence of common mental disorder was indicated in 48.6% of the mothers and there was an association between sociodemographic characteristics when the SRQ scores were correlated with the variable family income, marital status, maternal age and fatigue in the pandemic. Conclusion: the information in this research reaffirms the tiredness experienced by mothers in the face of the Coronavirus pandemic due to overload, due to multitasking, and variables such as: maternal age, presence of a partner and significant family (AU)